Influence of Yoga-Based Personality Development Program on Psychomotor Performance and Self-efficacy in School Children - Das, Madhusudan; Deepeshwar, Singh; Subramanya, Pailoor; Manjunath, Nandi Krishnamurthy (Frontiers in Pediatrics, 2016)
Selective attention and memory are the important components of scholastic performance in school children. While attempts are being made to introduce new methods to improve academic performance either as part of curricular or extra curricular activities in schools, the success rates are minimal cosidering an all round personality development. Hence, the present study assessed the effect of Yogä based intervention on psychomotor performance and behavioral changes in school children. Two hundred ten school children with ages ranging from 11-16 years (mean age ± SD; 13.7 ± 0.8 years) satisfying the inclusion and exclusion criteria were recruited for the 10 day Yogä program. An equal number of age matched participants (n=210; mean ± SD; 13.1 ± 0.8 years) selected for the control group. Participants were assessed for attention and performance using trail making task (TMT) and self-efficacy questionnaire (SEQ) at the beginning and end of ten days yoga practice. The yoga group showed higher self-efficacy and improved performance after 10 days. The performance in TMT A and B showed significantly higher number of attempts with a reduction in time taken to complete the task and number of wrong attempts compared to control group. Results suggests that Yogä practice enhances self-efficacy and processing speed with fine motor coordination, visual-motor integration, visual perception, planning ability and cognitive performance.